ANALISIS IMPLEMENTASI ALOKASI DANA DESA PADA KOTA LHOKSEUMAWE TAHUN 2015 - T. Fakhrial Dhani; Edi Suhaimi; T. Angga Maulana (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2016)
UU No. 6/ 2014 about village (Desa) and PP R.I No. 22/2015 about Village Money (Dana Desa/DD) which is funded by APBN, it could be positively in improving village development for getting infrastructure more better and contributing national economy impact. Detailed of DD for each districts should be allocate through fairness based on basic allocation and formula allocation, that counted by number of people, number of poverty, size of village and geographic reached index that distribute in phase one and two about 40% and phase three about 20%. Descriptive analytic through primer and secondary data used to gain the understanding of DD allocation for each sub district and dused to get the barriers of distribution phenomena in Lhokseumawe 2015. Lhokseumawe, one of districts in Aceh Province that covered 68 villages just got village money (DD) about 1.14% from Aceh Total. Detailed DD that received for 4 sub districts in Lhokseumawe, since the largest to smallest, Blang Mangat, Banda Sakti, Muara Dua and Muara Satu. Caused, Blang Mangat has 22 villages (dominant) compare than other components such as number of poverty, hardly index to reach the village, number of people and large of village. Transfer of Village money absolutely received lately by village authority in every phase. It caused by transfer lately from central/region government and also the complexity of documents disbursement in the first of village money national program. Due to the victorious goal of disbursement village money (DD), in the future transfer for village should be on time as UU said as well, and the villagers can use it as their initial action plan and also government should provide assistance by coming to each village for document disbursement and responsibility.